An aluminum alloy and a preparation method and application thereof
Patent Information
- Application Number
- CN202510754990.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-06-06
AI Technical Summary
经过挤压和拉拔硬化后,薄壁空心型材的室温抗拉强度很难达到140MPa,300℃时抗拉强度一般小于30MPa,弹性模量小于25GPa,无法满足电芯壳进一步轻量化及更高安全性能的要求
[0041]本发明的有益效果是:本发明通过优化铝合金的成分配比,使铝合金中形成了大量弥散分布的Al12(Fe,Mn)3Si等富铁强化相,有利于提高铝合金的在室温下和高温下的强度和弹性模量,具体为:铝合金经过挤压、拉拔加工后,H14态的薄壁空心型材的室温抗拉强度可以达到145MP以上,延伸率≥5.6%;300℃时抗拉强度可以达到50MPa以上,弹性模量可达到38Gpa。
Smart Images

Figure BDA0005438435780000071 
Figure BDA0005438435780000081 
Figure BDA0005438435780000091
Abstract
Description
Technical Field
[0001] This invention belongs to the field of alloys, specifically relating to an aluminum alloy, its preparation method, and its applications. Background Technology
[0002] 3xxx series aluminum alloys are aluminum-manganese rust-resistant aluminum alloys, belonging to the category of heat-treatable aluminum alloys. They possess advantages such as good corrosion resistance and weldability, high thermal conductivity, and excellent machinability, and are widely used in packaging materials, heat exchange materials, and other applications. 3003 alloy is a commonly used 3xxx series aluminum alloy. 3003 aluminum alloy ingots produced using a vertical semi-continuous casting method are extruded and drawn into square hollow profiles, which are widely used as cell shells for blade batteries in new energy vehicles. The room temperature and high temperature mechanical properties of the cell shell are crucial to the safety and lifespan of the blade battery. To achieve battery lightweighting and improve the driving range of new energy vehicles, the wall thickness of the cell shell is becoming increasingly thinner. To ensure battery safety, higher requirements are placed on the room temperature and high temperature mechanical properties of 3003 aluminum alloy.
[0003] Currently, the tensile strength of conventional 3003 aluminum alloy ingots after homogenization is generally less than 130 MPa, and the elongation is less than 20%. After extrusion and drawing hardening, the room temperature tensile strength of thin-walled hollow profiles is difficult to reach 140 MPa, the tensile strength at 300℃ is generally less than 30 MPa, and the elastic modulus is less than 25 GPa, which cannot meet the requirements for further lightweighting and higher safety performance of battery cell shells. Summary of the Invention
[0004] In order to overcome at least one of the technical problems existing in the prior art, one of the objectives of the present invention is to provide an aluminum alloy.
[0005] The second objective of this invention is to provide a method for preparing aluminum alloys.
[0006] The third objective of this invention is to provide a cell casing for automotive blade batteries.
[0007] The fourth objective of this invention is to provide a battery.
[0008] The fifth objective of this invention is to provide a new energy vehicle.
[0009] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0010] The first aspect of this invention provides an aluminum alloy composed of the following components by mass percentage: Mn 0.95–1.3%, Fe 0.45–0.75%, Si 0.15–0.3%, Cu 0.06–0.15%, Ti 0.015–0.03%, Zr 0.01–0.1%, Mg ≤0.02%, Zn ≤0.02%, B ≤0.02%, unavoidable impurities ≤0.12%, and the balance being Al. This invention, by optimizing the ratio of manganese, iron, silicon, and copper, facilitates the formation of fine, dispersed iron-containing high-temperature strengthening phases, thereby improving the high-temperature strength and high-temperature elastic modulus of the aluminum alloy. Furthermore, the addition of trace amounts of Ti and Zr elements to the aluminum alloy refines α-Al and promotes the precipitation of a second phase.
[0011] In some embodiments of the present invention, the aluminum alloy is composed of the following components in mass percentage: Mn 1.1–1.28%, Fe 0.6–0.62%, Si 0.21–0.29%, Cu 0.08–0.11%, Ti 0.018–0.022%, Zr 0.04–0.06%, Mg ≤0.012%, Zn ≤0.012%, B ≤0.003%, unavoidable impurities ≤0.12%, and the balance being Al.
[0012] In some embodiments of the present invention, the mass percentage of Mn can be selected from any value or a range formed by any two of the following: 0.95%, 0.97%, 1.0%, 1.02%, 1.05%, 1.07%, 1.09%, 1.10%, 1.12%, 1.14%, 1.15%, 1.17%, 1.19%, 1.20%, 1.22%, 1.24%, 1.25%, 1.27%, 1.29%, and 1.3%. Mn is a main alloying element; in aluminum alloys, besides increasing strength, it can also raise the recrystallization temperature of the alloy, preventing the formation of coarse recrystallized structures during extrusion. Mn has a low diffusion coefficient in aluminum alloys, resulting in severe dendrite segregation during solidification, requiring homogenization heat treatment. If the Mn content exceeds 1.3% or the homogenization heat treatment temperature is too low (e.g., below 600°C), a large amount of brittle A will form. l6 Mn or Al6(Fe,Mn) compounds can easily cause microcracks or cracks in the profiles during extrusion. If the Mn content is less than 0.95%, brittle iron compounds such as Al5(Fe,Si) will form in the casting structure, reducing the mechanical properties of the alloy.
[0013] In some embodiments of the present invention, the mass percentage of Fe can be selected from any value or a range formed by any two of 0.45%, 0.47%, 0.5%, 0.52%, 0.55%, 0.57%, 0.6%, 0.62%, 0.65%, 0.67%, 0.7%, 0.72%, and 0.75%. Fe can reduce the solid solubility of Mn in aluminum alloys, alleviate the degree of Mn dendrite segregation, and form a high-temperature strengthening phase. If the Fe content exceeds 0.75%, coarse Al6(Fe,Mn) compounds will be formed, reducing the strength and plasticity of the aluminum alloy. If the Fe content is below 0.45%, it will affect the high-temperature strength of the aluminum alloy.
[0014] In some embodiments of the present invention, the mass percentage of Si is any value or a range formed by any combination of 0.15%, 0.17%, 0.2%, 0.22%, 0.24%, 0.26%, 0.28%, and 0.3%. Si can improve the fluidity of aluminum alloy melt, thereby improving the casting performance of aluminum alloy, and also plays a role in solid solution strengthening. If the Si content is less than 0.15%, the solid solution strengthening effect on aluminum alloy is small. If the Si content is higher than 0.3%, needle-like silicon and Al6(Fe,Mn)Si compounds will precipitate in the casting structure, affecting the toughness of the alloy.
[0015] In some embodiments of the present invention, the mass percentage of Cu is any value of 0.06%, 0.08%, 0.10%, 0.12%, 0.14%, 0.15%, or a range formed by any combination of both. Cu can improve the tensile strength of aluminum alloys, but when the Cu content exceeds 0.15%, the corrosion resistance of the aluminum alloy decreases.
[0016] This invention requires controlling the content of element B to ≤0.003%, for example, it can be selected from any value among 0%, 0.001%, 0.002%, 0.003%, or any range formed by both. If the content of element B exceeds 0.003%, element B is prone to agglomeration in the aluminum alloy, and microcracks are easily formed at the agglomeration points during subsequent extrusion processing, resulting in a significant decrease in the mechanical properties of the aluminum alloy.
[0017] In some embodiments of the present invention, the sum of the mass percentages of Mg and Zn is ≤0.03%. The present invention strictly controls the content of Mg and Zn, ensuring that the sum of their mass percentages does not exceed 0.03%, thereby improving the weldability of aluminum alloys. If the individual content of Mg or Zn, or the total content of both, exceeds the range defined by the present invention, Mg and Zn are prone to volatilization at the weld pool during welding, forming microbubble defects that make the weld prone to pinholes, thus affecting the welding strength and weld appearance.
[0018] In some embodiments of the present invention, the mass percentage of Ti is any value or a range formed by any combination of 0.015%, 0.017%, 0.020%, 0.022%, 0.024%, 0.026%, 0.028%, and 0.03%. Trace amounts of Ti promote nucleation in aluminum alloys, thus refining α-Al dendrites. When the Ti content exceeds 0.03%, the viscosity of the molten pool increases during welding, leading to a decrease in weld quality.
[0019] In some embodiments of the present invention, the mass percentage of Zr is any value or a range formed by any combination of 0.01%, 0.02%, 0.04%, 0.06%, 0.08%, and 0.1%. Zr plays a refining role in the precipitates in aluminum alloys, while also improving the weldability of the aluminum alloys.
[0020] The second aspect of the present invention provides a method for preparing the aluminum alloy described in the first aspect of the present invention, comprising the following steps:
[0021] S1: The raw materials used to prepare aluminum alloys are melted and mixed to obtain aluminum alloy melt;
[0022] S2: Then, the aluminum alloy melt is cast into shape using a vertical semi-continuous casting method. The cooling rate during casting is 40-60℃ / s to obtain a cast rod.
[0023] S3: The casting rod is subjected to homogenization heat treatment and then cooled;
[0024] The homogenization heat treatment steps are as follows: first, keep the temperature at 600-610℃ for 6-8 hours, then raise the temperature to 625-635℃ and keep it at 600-610℃ for 1-2 hours, and then cool it with air or water mist.
[0025] In some embodiments of the present invention, the preparation method further includes a step S4 after step S3, wherein step S4 is: heating and extruding into a hollow profile, and then drawing to the H14 state to obtain the aluminum alloy; in some embodiments of the present invention, step S4 is: heating to 450-500°C and then extruding into a hollow profile, and then drawing to the H14 state to obtain the aluminum alloy.
[0026] In some embodiments of the present invention, the cooling rate during casting can be selected from any value or a range formed by any two of the following: 40℃ / s, 42℃ / s, 44℃ / s, 46℃ / s, 48℃ / s, 50℃ / s, 52℃ / s, 54℃ / s, 56℃ / s, 58℃ / s, and 60℃ / s. Existing technologies generally employ relatively low cooling rates (≤30℃ / s) during vertical semi-continuous casting of 3xxx series aluminum alloys. The present invention improves the cooling rate during casting (cooling rate refers to the cooling speed of the aluminum alloy melt from the casting temperature to the solidus line, based on the cooling rate at the core of the ingot). This refines the grain size and second phase particle size of the aluminum alloy ingot and increases the solid solubility of Mn within the grains, laying the foundation for subsequent homogenization heat treatment to adjust the type of the second phase compound. The present invention adjusts the cooling rate during casting by regulating parameters such as casting temperature, casting speed, cooling water volume, cooling water temperature, and cooling water pressure.
[0027] In some embodiments of the present invention, the homogenization heat treatment step is as follows: first, holding at 600–610°C (e.g., 600°C, 602°C, 604°C, 606°C, 608°C, or 610°C) for 6–8 hours (e.g., 6 hours, 6.5 hours, 7 hours, 7.5 hours, or 8 hours), then raising the temperature to 625–635°C (e.g., 625°C, 628°C, 630°C, 632°C, 634°C, or 635°C) and holding for 1–2 hours (e.g., 1 hour, 1.5 hours, or 2 hours), followed by air cooling or water mist cooling. The present invention uses the above-mentioned homogenization heat treatment to cause the Al precipitated in the aluminum alloy material... 12 The average particle size of the second phase, such as (Fe,Mn)3Si, is ≤1μm. Al 12 (Fe,Mn)3Si exhibits good high-temperature stability and possesses a self-lubricating effect during extrusion and drawing, preventing orange peel defects from forming on the profile surface. Furthermore, the aforementioned homogenization heat treatment allows the aluminum alloy to achieve an elongation exceeding 40%, which is beneficial for subsequent extrusion and drawing. Although the strength decreases during the homogenization heat treatment and extrusion stages, it can be significantly improved through work hardening during drawing.
[0028] In existing technologies for producing 3003 aluminum alloy ingots using vertical semi-continuous casting, the slow diffusion rate of Mn leads to its supersaturated solidification within the aluminum alloy during solidification, resulting in severe Mn dendrite segregation in Al-Mn alloys. This necessitates a lengthy (approximately 20 hours) single-stage homogenization heat treatment before extrusion, resulting in high energy consumption. During development, the inventors discovered that single-stage homogenization heat treatment cannot simultaneously increase the amount of precipitated second phase while reducing its particle size. The long treatment time allows the generated second phase to grow larger, forming coarse phases. These coarse phases can cause localized stress concentration during the drawing process of hollow profiles formed from extruded aluminum alloys, leading to breakage and hindering effective drawing. Furthermore, the elongation of aluminum alloys after single-stage homogenization heat treatment is typically ≤20%, resulting in reduced strength and elongation after subsequent extrusion and making the profiles prone to orange peel texture and breakage during drawing deformation. Therefore, after repeated attempts to overcome the shortcomings of single-stage homogenization heat treatment, the inventors finally discovered that using a two-stage (two-stage means performing heat treatment at one fixed temperature first, and then at another fixed temperature) homogenization heat treatment method, where the first stage of homogenization heat treatment is performed at a lower temperature, followed by a second stage of homogenization heat treatment at a higher temperature, can significantly shorten the homogenization time (homogenization heat treatment can be completed in 7-10 hours). The higher temperature of the second stage homogenization heat treatment is conducive to the dissolution of coarse second phases, thereby avoiding the presence of coarse second phases in the aluminum alloy. In addition, the shorter homogenization heat treatment time prevents the precipitated second phase from gradually growing during the long homogenization heat treatment process.
[0029] In some embodiments of the present invention, the temperature of the aluminum alloy melt is 730–760°C.
[0030] In some embodiments of the present invention, the casting speed during casting is 160-200 mm / min.
[0031] In some embodiments of the present invention, the aluminum alloy melt is prepared by a method comprising the following steps:
[0032] Some of the raw materials used to prepare the aluminum alloy are heated to 730-760°C to melt, and then aluminum-titanium master alloy and aluminum-zirconium master alloy are added in sequence and melted and mixed. The mixture is then refined and slag is removed to obtain the aluminum alloy melt.
[0033] Some of the raw materials used to prepare aluminum alloys include aluminum ingots, aluminum-manganese master alloys or manganese agents, aluminum-iron master alloys or iron metals, aluminum-copper master alloys or copper metals, and aluminum-silicon master alloys or silicon particles.
[0034] The aluminum-zirconium master alloy in this invention needs to be added after the aluminum-titanium master alloy. If the order of addition is reversed, the refining effect of Ti will be significantly reduced.
[0035] In this invention, Mg, Zn and B are impurity elements in the raw materials. There is no need to add Mg source, Zn source and B source during the preparation process. However, it is necessary to control the content range of Mg, Zn and B in the aluminum alloy so that the content of these three elements does not exceed the range defined by this invention. Otherwise, it will cause a decrease in the performance of the aluminum alloy.
[0036] In some embodiments of the present invention, some of the raw materials used to prepare the aluminum alloy include aluminum ingots, aluminum-manganese master alloys, aluminum-iron master alloys, aluminum-copper master alloys, and aluminum-silicon master alloys.
[0037] In some embodiments of the present invention, the refining process employs high-purity nitrogen gas.
[0038] A third aspect of the invention provides a cell casing for an automotive blade battery, comprising the aluminum alloy described in the first aspect of the invention.
[0039] A fourth aspect of the present invention provides a battery comprising a cell casing as described in the third aspect of the present invention, or an aluminum alloy as described in the first aspect of the present invention.
[0040] A fifth aspect of the present invention provides a new energy vehicle, comprising the battery described in the fourth aspect of the present invention, or the aluminum alloy described in the first aspect of the present invention.
[0041] The beneficial effects of this invention are: by optimizing the composition ratio of aluminum alloy, this invention enables the formation of a large number of dispersed Al atoms in the aluminum alloy. 12 Iron-rich strengthening phases such as (Fe,Mn)3Si are beneficial to improving the strength and elastic modulus of aluminum alloys at both room temperature and high temperature. Specifically, after extrusion and drawing, the room temperature tensile strength of thin-walled hollow profiles in the H14 state can reach more than 145 MPa, with an elongation of ≥5.6%; the tensile strength at 300℃ can reach more than 50 MPa, and the elastic modulus can reach 38 GPa.
[0042] Furthermore, the preparation method of this invention employs a high cooling rate and a two-stage homogenization heat treatment process during casting, which allows for the control of grain size, grain boundaries, and the density and size of intragranular precipitates. On the one hand, this suppresses the formation of coarse second phases, preventing material failure due to stress concentration; on the other hand, it forms a large number of dispersed Al atoms. 12 Iron-rich strengthening phases such as (Fe,Mn)3Si are beneficial for improving the high-temperature strength and elastic modulus of the alloy. Attached Figure Description
[0043] Figure 1The image is a 1000x magnified SEM image of the casting rod obtained in step (2) of Example 1.
[0044] Figure 2 The image is a 5000x magnified SEM image of the casting rod obtained in step (2) of Example 1.
[0045] Figure 3 This is a 1000x magnified SEM image of the aluminum alloy prepared in Example 1.
[0046] Figure 4 This is a 5000x magnified SEM image of the aluminum alloy obtained in Example 1.
[0047] Figure 5 The image is a 5000x magnified SEM image of the casting rod obtained in step (2) of Comparative Example 3.
[0048] Figure 6 The image is a 2000x magnified SEM image of the casting rod obtained in step (2) of Comparative Example 5.
[0049] Figure 7 The image shows the SEM image of the weld seam after high-frequency welding of the drawn hollow profile made of the aluminum alloy in Example 1. Detailed Implementation
[0050] The specific implementation of the present invention will be further described in detail below with reference to the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that any processes not specifically described in detail below are those that can be implemented or understood by those skilled in the art by referring to the prior art. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0051] The raw material information used in the following examples and comparative examples is as follows:
[0052] In the AlMn10 master alloy, the mass percentage of Mn is 10% and the mass percentage of Al is 90%.
[0053] In the AlFe10 master alloy, the mass percentage of Fe is 10% and the mass percentage of Al is 90%.
[0054] In the AlCu50 master alloy, the mass percentage of Cu is 50% and the mass percentage of Al is 50%.
[0055] In the AlTi10 master alloy, the mass percentage of Ti is 10% and the mass percentage of Al is 90%.
[0056] In the AlZr10 master alloy, the mass percentage of Zr is 10% and the mass percentage of Al is 90%.
[0057] In the AlSi20 master alloy, the mass percentage of Si is 20% and the mass percentage of Al is 80%.
[0058] Example 1
[0059] This example provides an aluminum alloy composed of the following components by mass percentage:
[0060] Mn 1.1%, Fe 0.6%, Si 0.22%, Cu 0.1%, Ti 0.02%, Zr 0.05%, Mg 0.01%, Zn 0.012%, B 0.002%, other impurities ≤0.12%, balance Al.
[0061] This example provides a method for preparing an aluminum alloy, specifically including the following steps:
[0062] (1) According to the composition and proportion of the alloy in Example 1 in Table 1, aluminum ingots with a purity of 99.8%, AlSi20 master alloy, AlMn10 master alloy, AlFe10 master alloy, and AlCu50 master alloy were added to a gas-heated melting furnace for melting. Among them, B, Mg, and Zn are impurity elements in the raw materials and do not need to be added separately. It is only necessary to control their content within the range of the present invention. When the melt temperature reaches 750°C, AlTi10 alloy is added to the melting furnace for melting. Then, the electromagnetic stirring device at the bottom of the melting furnace is started to stir the melt evenly. Then, AlZr10 alloy is added, and after stirring evenly again, the melt is refined by adding commercially available aluminum alloy refining agent with high-purity nitrogen. After refining, the slag is removed, and after standing for 30 minutes, semi-continuous casting is started.
[0063] (2) During casting, the temperature of the melt in the furnace was 740℃, the pressure of the cooling water was 120kPa, the temperature of the cooling water was 5℃, the casting speed was 180mm / min, and the cooling rate of the core of the casting rod was measured to be 50℃ / s by embedding a thermocouple in the casting rod. A casting rod with a diameter of 127mm was prepared.
[0064] (3) The casting rod prepared in step (2) is subjected to a two-stage homogenization heat treatment. The specific process is as follows: first, the temperature is raised to 605℃ and held for 7 hours; then the casting rod is raised to 630℃ and held for 1.5 hours, and then cooled by water mist cooling to obtain the aluminum alloy in this example.
[0065] Examples 2-12
[0066] The only difference between the preparation methods of the aluminum alloys in Examples 2 to 12 and those in Example 1 is that the composition ratio of the aluminum alloys is different. Examples 2 to 12 respectively use the composition ratio of the aluminum alloys corresponding to Examples 2 to 12 in Table 1.
[0067] Comparative Examples 1-9
[0068] The only difference between the preparation methods of the aluminum alloys in Comparative Examples 1 to 9 and those in Example 1 is that the composition ratio of the aluminum alloys is different. Comparative Examples 1 to 9 adopt the composition ratio of the aluminum alloys corresponding to Comparative Examples 1 to 9 in Table 1.
[0069] Table 1. Composition ratios of aluminum alloys in Examples 1-12 and Comparative Examples 1-9
[0070]
[0071] Comparative Example 10
[0072] The only difference between the aluminum alloy preparation method in this example and that in Example 1 is that in step (2) the cooling rate of the core of the casting rod is 65℃ / s by adjusting the cold water pressure, temperature and casting speed. The specific parameters are: adjusting the cold water pressure to 135kPa, the cold water temperature to 3.2℃ and the casting speed to 197mm / min.
[0073] Comparative Example 11
[0074] The only difference between the aluminum alloy preparation method in this example and that in Example 1 is that in step (2) of this example, the cooling rate of the core of the casting rod is 35℃ / s by adjusting the cold water pressure, temperature and casting speed. The specific parameters are: adjusting the cold water pressure to 96kPa, the cold water temperature to 15.4℃ and the casting speed to 155mm / min.
[0075] Comparative Example 12
[0076] The only difference between the aluminum alloy preparation method in this example and that in Example 1 is that step (3) in this example adopts a single-stage homogenization process, specifically: at 600℃, it is kept at a temperature of 20h, and then cooled by water mist cooling.
[0077] Comparative Example 13
[0078] The only difference between the aluminum alloy preparation method in this example and that in Example 1 is that the casting rod in step (3) of this example adopts a two-stage homogenization process. The specific process is as follows: first, it is kept at 630℃ for 1.5h, then cooled to 605℃ for 7h, and then cooled by water mist cooling.
[0079] Comparative Example 14
[0080] The only difference between the aluminum alloy preparation method in this example and that in Example 1 is that in step (1) of this example, when the melt temperature reaches 750°C, the AlZr10 master alloy is added to the furnace for melting, and then the electromagnetic stirring device at the bottom of the furnace is activated to stir the melt evenly. Then the AlTi10 master alloy is added.
[0081] Performance testing
[0082] (1) Room temperature mechanical property testing
[0083] Samples were taken from the cast rods (i.e., as-cast state) with a diameter of 127 mm obtained in step (2) of Examples 1-12 and Comparative Examples 1-14 and the aluminum alloy (i.e., homogenized state) obtained in step (3), respectively, and then room temperature mechanical property tests were performed. The test standards for tensile strength and yield strength were in accordance with GB / T16865-2013, and the test standards for elongation after fracture were in accordance with GB / T16865-2013. The specific test results are shown in Table 2.
[0084] Table 2. Results of room temperature mechanical properties test of cast rods
[0085]
[0086]
[0087] As shown in Table 2, the room temperature yield strength of the 127mm diameter cast rod (i.e., as-cast state) obtained in step (2) of Examples 1-12 of the present invention is 76-89MPa, the room temperature tensile strength is 128-152MPa, and the room temperature elongation is 20-27%; the room temperature yield strength of the aluminum alloy (i.e., homogenized state) obtained in step (3) is 71-84MPa, the room temperature tensile strength is 123-135MPa, and the room temperature elongation is 40-47%. By comparing the mechanical properties of the as-cast state and the homogenized state, it can be seen that the elongation of the aluminum alloy after the cast rod obtained in step (2) is significantly improved, which is beneficial to subsequent extrusion and drawing processes and avoids adverse conditions such as orange peel, cracks, splitting, and breakage during extrusion and drawing.
[0088] The room temperature yield strength of the cast rod (i.e., as-cast state) with a diameter of 127 mm obtained in Comparative Examples 1 to 14 is 52 to 72 MPa, the room temperature tensile strength is 108 to 128 MPa, and the room temperature elongation is 14.3 to 25%. The room temperature yield strength of the aluminum alloy (i.e., homogenized state) obtained in step (3) is 40 to 55 MPa, the room temperature tensile strength is 98 to 112 MPa, and the room temperature elongation is 29 to 39%. It can be seen that the performance of the aluminum alloy in both the as-cast state and the homogenized state in Comparative Examples 1 to 14 is significantly worse than that in Examples 1 to 12. This indicates that if the content of any component or the range of any parameter is not within the range defined by the present invention, the performance of the obtained aluminum alloy will be significantly reduced.
[0089] Compared to Example 1, the cooling rate of Comparative Example 10 was too high to allow for casting; the cooling rate of Comparative Example 11 was slow, and the properties of the aluminum alloy in both the as-cast and homogenized states were significantly inferior to those of Example 1. This was because the grain size and the amount of precipitated second phase became coarser, resulting in a decrease in precipitate density. Comparative Example 12 used a single-stage homogenization process, and Comparative Example 13 adjusted the temperature of the two-stage homogenization process. The properties of the aluminum alloys obtained in both Comparative Examples 12 and 13 in both the as-cast and homogenized states were significantly inferior to those of Example 1. This was because the amount of precipitated second phase became coarser, resulting in a decrease in precipitate density.
[0090] (2) Organizational Characteristic Test
[0091] Samples were taken from half the radius of the cross-section of the 127 mm diameter cast rods (i.e., as-cast state) obtained in step (2) of Examples 1-12 and Comparative Examples 1-14. The average grain size was determined using electron backscatter diffraction (EBSD) according to GB / T38532-2020. Then, the size of the second phase precipitated within and at the grain boundaries of the aluminum alloy (i.e., homogenized state) obtained after the double-stage homogenization heat treatment in step (3) was determined using scanning electron microscopy (SEM). Specifically, at least 10 fields of view were randomly photographed using a scanning electron microscope (SEM) at a magnification of 20,000. The images were observed and analyzed, and the maximum length of the second phase within the grain was taken as the diameter. At least 5 particles were randomly measured in each field of view. The average size of all measured particles was then calculated to obtain the average diameter of the particles within the grain. The number of second phase particles in each field of view was counted, and the distribution density of the second phase was calculated by considering the area of the photographed field. The sample was randomly photographed using a scanning electron microscope (SEM) at a magnification of 500x, with more than 10 fields of view. The images were observed and analyzed, and the maximum length of the second phase at the grain boundary was taken as the diameter. More than 5 particles were randomly measured in each field of view. The average diameter of all measured particles was then obtained. The data of the grain size in the cast state and the second phase in the homogenized state, measured according to the above test method, are shown in Table 3 below.
[0092] Table 3 Microstructural characteristics of the as-cast and homogenized states
[0093]
[0094]
[0095] As shown in Table 3, compared with Comparative Examples 1-14, the as-cast grain size (17.3-18.8 μm) of the aluminum alloys prepared in Examples 1-12 was reduced, and the intragranular precipitate density of the second phase in the homogenized state was (1.15 × 10⁻⁶). 8 ~1.35×10 8 mm 2The average diameter of the second phase precipitated within the grains (161–198 nm) and the average diameter of the second phase precipitated at grain boundaries (1.76–1.93 μm) are significantly reduced, controlling the average grain size of the as-cast state below 20 μm and the grain size of the second phase precipitated at grain boundaries below 2 μm, thus achieving the goal of fine grains and strengthening the aluminum alloy. In this invention, after a two-stage homogenization heat treatment, the grain size of the aluminum alloy is basically the same as that in the as-cast state, but the elemental distribution in the aluminum alloy is more uniform, the size of the second phase at grain boundaries is significantly smaller than that in the as-cast state, and a large amount of Al is precipitated. 12 The (Fe,Mn)3Si phase exhibits higher high-temperature stability, while a large number of nano-sized precipitates are formed inside the grains, which plays a role in dispersion strengthening of aluminum alloys.
[0096] Comparative Example 8, which does not contain titanium, and Comparative Example 9, which does not contain zirconium, produced aluminum alloys with larger grain sizes, lower density of the precipitated second phase, and larger second phase size. This shows that titanium and zirconium work synergistically to refine α-Al grains and promote the precipitation of the second phase in the aluminum alloy.
[0097] (3) Room temperature mechanical properties of hollow profiles
[0098] The aluminum alloy cast rods obtained after homogenization heat treatment in step (3) of Examples 1-12 and Comparative Examples 1-14 were heated to 470°C and then extruded into hollow profiles with a wall thickness of 0.4 mm (i.e., extruded state). The hollow profiles were then drawn at room temperature to the H14 state (i.e., H14 state). Samples were taken from the extruded and drawn hollow profiles for room temperature mechanical property testing. The specific test results are shown in Table 4.
[0099] Table 4. Room temperature mechanical properties of hollow profiles
[0100]
[0101]
[0102] As shown in Table 4, the aluminum alloys obtained in Examples 1-12 exhibited good extrusion and drawing performance. The room temperature yield strength of the extruded state was 69-78 MPa, the tensile strength was 124-133 MPa, and the elongation was 20-28%. The room temperature yield strength of the H14 state was 135-145 MPa, the tensile strength was 147-165 MPa, and the elongation was 5.6-6.7%. In other words, the room temperature mechanical properties of the aluminum alloys obtained in Examples 1-12 in both the extruded and H14 states were significantly higher than those in Comparative Examples 1-14.
[0103] Samples were taken from the hollow profiles in the H14 state (i.e., H14 condition) after drawing in Examples 1, 5, 6, 8, 11 and Comparative Example 13, and the room temperature elastic modulus was tested. The test standard was in accordance with GB / T 22315-2008. The specific test results are shown in Table 5.
[0104] Table 5. Room temperature elastic modulus data for hollow profiles
[0105] Example 1 69.9 Example 5 69.7 Example 6 69.8 Example 8 69.5 Example 11 69.4 Comparative Example 13 68.5
[0106] As shown in Table 5, the elastic modulus of the hollow profiles in the embodiments and comparative examples of the present invention is not significantly different at room temperature.
[0107] (4) High-temperature mechanical property testing
[0108] Samples were taken from the hollow profiles in the H14 state (i.e., H14 condition) after drawing in Examples 1, 5, 6, 8, 11 and Comparative Example 13 above, and mechanical properties were tested at 300℃. The test standard was in accordance with DIN EN ISO 6892-2. The specific test results are shown in Table 6.
[0109] Table 6 Mechanical property data of hollow profiles
[0110]
[0111]
[0112] As shown in Table 6, after the aluminum alloys in Examples 1 to 12 of the present invention are drawn to the H14 state, the yield strength of the aluminum alloys at a high temperature of 300°C is 36 to 42 MPa, the tensile strength is 43 to 49 MPa, and the elastic modulus is 38.2 to 39.5 GPa, which are significantly higher than the aluminum alloys obtained in Comparative Examples 1 to 14.
[0113] Compared with Example 1, Comparative Example 13 only changed the heat treatment temperature and heat treatment time of the two-stage homogenization heat treatment step, and the yield strength, tensile strength and elastic modulus of the aluminum alloy obtained at 300°C were significantly reduced.
[0114] (5) Weld quality evaluation test
[0115] Samples were taken from the H14 state hollow profiles (i.e., H14 condition) after drawing in Examples 1, 10, and Comparative Example 11, and welding experiments were conducted using laser welding. Weld quality was evaluated from three aspects: weld uniformity, weld cracks, and porosity defects. The welding process parameters were: power 1500W, welding speed 40mm / s, decoking amount -1mm, shielding gas Ar, and gas flow rate 20L / min. Specific test results are shown in Table 7 below.
[0116] Table 7 Weld Quality Evaluation
[0117] Example 1 Uniform appearance none none Example 10 Uniform appearance none none Comparative Example 11 Uniform appearance none There are a large number of pinholes
[0118] As shown in Table 7, compared with Comparative Example 11, the aluminum alloy prepared by the present invention has better weld appearance uniformity during laser welding, and there are no cracks or pore defects at the weld, which indicates that the aluminum alloy in the present invention can be used for battery cell shells.
[0119] (6) Surface morphology test
[0120] The SEM image of the cast rod obtained in step (2) of Example 1 was tested using scanning electron microscopy. The specific test results are as follows: Figure 1 and Figure 2 As shown. Among them, Figure 1 This is a SEM image magnified 1000 times. Figure 2 This is an SEM image magnified 5000 times. (From...) Figure 1 and Figure 2 It can be seen that the grains (α-aluminum) are uniform and fine, and the second phase (e.g., Al) 12 (Fe,Mn)3Si, etc., precipitate at grain boundaries in a discontinuous distribution.
[0121] The SEM image of the aluminum alloy obtained in step (3) of Example 1 was tested using scanning electron microscopy. The specific test results are as follows: Figure 3 and Figure 4 As shown. Among them, Figure 3 This is a SEM image magnified 1000 times. Figure 4 This is an SEM image magnified 5000 times. (From...) Figure 3 and Figure 4 It can be seen that after the casting rod undergoes two-stage homogenization heat treatment, the second phase on the grain boundary becomes finer, and a large amount of nanoscale second phase precipitates within the grain.
[0122] The SEM image of the cast rod prepared in step (2) of Comparative Example 3, magnified 5000 times, was obtained using scanning electron microscopy. See details below. Figure 5 As shown, by Figure 5 It can be seen that the aluminum alloy in Comparative Example 3 contains coarse iron-rich compounds.
[0123] The SEM image of the cast rod prepared in step (2) of Comparative Example 5, magnified 2000 times, was obtained using scanning electron microscopy. (See details below.) Figure 6 As shown, by Figure 6 It can be seen that a large amount of silicon phase precipitated in the aluminum alloy of Comparative Example 5, and there are microcracks between it and the aluminum matrix.
[0124] The SEM images of the drawn hollow profile made of the aluminum alloy in Example 1 after laser welding were obtained using scanning electron microscopy, as shown in the following figures. Figure 7 As shown, by Figure 7 It can be seen that the structure at the weld is uniform and free from defects such as porosity and inclusions.
[0125] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. An aluminum alloy, characterized in that: The aluminum alloy is composed of the following components by mass percentage: Mn 1.1~1.28%, Fe 0.6~0.62%, Si 0.21~0.29%, Cu 0.08~0.11%, Ti 0.018~0.022%, Zr 0.04~0.06%, Mg≤0.012%, Zn≤0.012%, B≤0.003%, unavoidable impurities ≤0.12%, and the balance being Al; The aluminum alloy is prepared by a method including the following steps: S1: The raw materials used to prepare aluminum alloys are melted and mixed to obtain aluminum alloy melt; S2: Then, the aluminum alloy melt is cast into shape using a vertical semi-continuous casting method. The cooling rate during casting is 40~60℃ / s to obtain a cast rod. S3: The casting rod is subjected to homogenization heat treatment and then cooled; The homogenization heat treatment steps are as follows: first, keep the temperature at 600~610℃ for 6~8 hours, and then raise the temperature to 625~635℃ and keep it at 1~2 hours; The aluminum alloy melt is prepared by a method including the following steps: Some of the raw materials used to prepare the aluminum alloy are heated to 730~760℃ to melt, and then aluminum-titanium master alloy and aluminum-zirconium master alloy are added in sequence and melted and mixed. The mixture is then refined and slag is removed to obtain the aluminum alloy melt.
2. The aluminum alloy according to claim 1, characterized in that: Some of the raw materials used to prepare aluminum alloys include aluminum metal, aluminum-manganese master alloy or manganese metal, aluminum-iron master alloy or iron metal, aluminum-copper master alloy or copper metal, aluminum-silicon master alloy or silicon particles.
3. The method for preparing the aluminum alloy according to any one of claims 1 to 2, characterized in that: Includes the following steps: S1: The raw materials used to prepare aluminum alloys are melted and mixed to obtain aluminum alloy melt; S2: Then, the aluminum alloy melt is cast into shape using a vertical semi-continuous casting method. The cooling rate during casting is 40~60℃ / s to obtain a cast rod. S3: The casting rod is subjected to homogenization heat treatment and then cooled; The homogenization heat treatment steps are as follows: first, keep the temperature at 600~610℃ for 6~8 hours, and then raise the temperature to 625~635℃ and keep it at 1~2 hours; The aluminum alloy melt is prepared by a method including the following steps: Some of the raw materials used to prepare the aluminum alloy are heated to 730~760℃ to melt, and then aluminum-titanium master alloy and aluminum-zirconium master alloy are added in sequence and melted and mixed. The mixture is then refined and slag is removed to obtain the aluminum alloy melt.
4. The method for preparing the aluminum alloy according to claim 3, characterized in that: The casting speed during casting is 160~200 mm / min.
5. The method for preparing the aluminum alloy according to claim 3, characterized in that: The preparation method further includes a step S4 after step S3; step S4 is: heating and extruding into a hollow profile, and then drawing to the H14 state.
6. The method for preparing the aluminum alloy according to claim 3, characterized in that: Some of the raw materials used to prepare aluminum alloys include aluminum metal, aluminum-manganese master alloy or manganese metal, aluminum-iron master alloy or iron metal, aluminum-copper master alloy or copper metal, aluminum-silicon master alloy or silicon particles.
7. A cell casing for an automotive blade battery, characterized in that: Includes the aluminum alloy described in any one of claims 1 to 2.
8. A battery, characterized in that: It includes the cell casing as described in claim 7, or the aluminum alloy as described in any one of claims 1 to 2.
9. A new energy vehicle, characterized in that: Includes the battery as described in claim 8, or the aluminum alloy as described in any one of claims 1 to 2.
Citation Information
Patent Citations
Aluminum profile and machining method and application thereof
CN108774697A
Aluminum-manganese alloy extruded material as well as preparation method and application thereof
CN116005042A
Preparation method and application of power battery shell
CN116219354A